Modernisasi Pendidikan Islam Di Madrasah - Anggrina, Safa; Silalahi, Maqhfira Ikhwana; Napitupulu, Fazriah Aulia (EL-EMIR Institute, 2025)
Modernization of Islamic education is one of the educational efforts to balance the current developments without having to abandon the basic principles of Islam. Modernization of Islamic education in madrasas is also a process of adjusting the education system to be in line with current educational developments. This study aims to analyze the forms, strategies, and challenges of modernizing Islamic education among madrasas. Modernization of Islamic education in madrasas is a response to changes in the times and increasingly rapid technological developments. This change not only touches on the curriculum aspect, but also concerns learning methods, the use of information technology, and improving teacher competence. This study uses a qualitative approach with a descriptive method. This approach was chosen because it is appropriate to describe in depth the process, challenges, and strategies of modernizing Islamic education that occur in the madrasa environment. The results of the analysis show that although many madrasas have innovated, there are still obstacles such as limited facilities, low digital literacy, and resistance to change.